CryoEM Reveals the Complexity and Diversity of ATP Synthases - Courbon, Gautier M.; Rubinstein, John L. (Frontiers in Microbiology, 2022)
During respiration, ATP synthases harness the electrochemical proton motive force generated by the electron transport chain to synthesize ATP. These macromolecular machines function by a remarkable rotary catalytic mechanism that couples proton translocation to rotation of a rotor subcomplex, and rotation to the synthesis of ATP. Initially, X-ray crystallography was the only way to gain insight into the structure of ATP synthases and provided ground-breaking insight into the soluble parts of the complex that explained the catalytic mechanism by which rotation is coupled to ATP synthesis. In contrast, early electron microscopy was limited to studies of the overall shape of the assembly. However, advances in electron cryomicroscopy (cryoEM) have allowed high-resolution structure determination including the membrane region of ATP synthase. These studies, reviewed here, have revealed the high-resolution structures of the remaining ATP synthase subunits and shown how these subunits work together in the intact macromolecular machine. CryoEM continues to uncover the diversity of ATP synthase structures across species and has begun to show how ATP synthases can be targeted by therapeutics to treat human disease.